Burrowing and unburrowing in submerged granular media through fluidization and shape-change - Nayak, Aniruddha; Seo, Hoseung; Gravish, Nick; Tolley, Michael T. (Frontiers in Robotics and AI, 2025)
Subterranean exploration in submerged granular media (GM) presents significant challenges for robotic systems due to high drag forces and the complex physics of GM. This paper introduces a robotic system that combines water-jet-based fluidization for self-burrowing in submerged environments and an untethered, volume-change mechanism for burrowing out. The water-based fluidization approach significantly reduces drag on the robot, allowing it to burrow into GM with minimal force. To burrow out, the robot uses a soft, inflatable bladder that undergoes periodic radial expansion, inspired by natural systems such as razor clams. Experimental results demonstrate that increased water flow rates accelerate the burrowing process, while the unburrowing mechanism is effective at varying depths. Comparisons between pneumatic and hydraulic untethered systems highlight trade-offs in terms of operational time and unburrowing speed. This work advances the capabilities of robots in underwater environments, with potential applications in environmental monitoring and underwater archaeology.